Microwave Analysis for Two-Dimensional C-V and Noise Model of AlGaN/GaN MODFET - Ramnish Kumar; Sandeep K. Arya; Anil Ahlawat (Advances in Materials Science and Engineering)
A new two-dimensional analytical model for the capacitance-voltage and noise characteristics of a AlGaN/GaN MODFET is developed. The two-dimensional electron gas density is calculated as a function of device dimensions. The model includes the spontaneous and polarization effects. The contribution of various capacitances to the performance of the device is shown. The model further predicts the transconductance, drain conductance, and frequency of operation. A high transconductance of 160 mS/mm and a cut-off frequency of 11.6 GHz are obtained for a device of 50 nm gate length. The effect of gate length on the gate length behaviour of the noise coefficients P, R, and C is also studied. The effect of parasitic source and gate resistance has also been studied to evaluate the minimum noise figure. The excellent agreement with the previously simulated results confirms the validity of the proposed model to optimize the device performance at high frequencies.